Entrepreneurs' Human Capital as a Decision Criterion among Venture Capital Funds - Morawczyński, Rafał (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The article is a review of research on the importance of human capital for the assessment of entrepreneurs by venture capital funds. Theories that underpin the study of this problem - the theory of human capital theory, the theory of the firm and its chief executives - are the starting point. The characteristics of entrepreneurs, managers and their teams used to measure the quality of this capital in the decisions taken by venture capital are discussed, as are the conditions of this assessment, including the life cycle of the company, industry, country, and the uniqueness of the investment process and the relationship of these characteristics to the performance of firms. The paper also shows the evolution of research in this field, including the latest concepts from a psychological critique of the concept of bounded rationality. The article argues that human capital is rightly seen as one of the most important decision criteria used by venture capital funds.